Bottom-Up Synthesis of Nitrogen-Doped Polycyclic Aromatic Hydrocarbons - Liu, Junzhi; Feng, Xinliang (Synlett, 2020)
Bottom-up organic synthesis serves as an efficient method to provide atomically precise heteroatom-doped polycyclic aromatic hydrocarbons (PAHs) with not only well-defined size and edge structures but also specific concentrations and positions of the heteroatoms. We provide a plenary account of the preparation of nitrogen-doped PAHs (N-PAHs) through 1,3-dipolar cycloaddition between different dipolarophiles, as well as pyrazine-type N-doped diaza-hexa-peri-hexabenzocoronene (diaza-HBC). Additionally, we present the synthesis of a class of helical N-charged PAHs, including one charged aza[5]helicene and two charged aza[4]helicenes. Moreover, the bottom-up organic synthesis strategy is further extended to the construction of novel nitrogen-boron-nitrogen (NBN)-containing PAHs. Finally, we discuss the synthesis of four-coordinate boron chromophores containing 6,12,18-tris(alkyl amine)-5,11,17-triazatrinaphthylene derivative ligands.1 Introduction2 Nitrogen-Doped PAHs Based on Dibenzo-9a-azaphenalene (DBAP)3 Cationic Nitrogen-Doped Helical PAHs4 Nitrogen–Boron–Nitrogen-Doped PAHs5 Conclusion and Outlook
Keywords: polycyclic aromatic hydrocarbons; nanographenes; heteroatoms; nitrogen doping; boron doping